Metode Speak Up untuk Meningkatkan Interprofesional Collaboration Practice - Yuliana Yuliana; Rr. Tutik Sri Hariyati; La Ode Abdul Rahman; Cori Tri Suryani; Herawani Azis (Jurnal Keperawatan Silampari, 2021)
This study aims to identify problems and develop nurse improvement strategies to speak up in IPCP. The method used in this research is an improvement program based on innovation development with a pilot project approach. The results showed that the characteristics of the respondents in the survey of nurse satisfaction in IPCP conducted during problem identification were that there were more female nurses (91%) than male nurses (9.3%), the age of the most respondents was between 21-30 years. (44%), and age 31 -40 years (33%) or productive age. The education level of most respondents is D3 (83%), the second is Nurses (23%). Respondent's competency level for PK I (25%), PK II (32%), PK III (45%), and PK IV (4%). Most of the respondents who participated in this survey were Associate Nurse (PA) at 91% and Primary Nurse (PP) at 14%. In conclusion, the speak-up method can improve nursing services, the image of the nursing profession, and the achievement of patient safety. Keywords: Patient Safety, Interprofessional Collaborative Practice, Speak Up